How Do Digital Literacy Affect Millennial Investment in Sharia Capital Markets? The Role of Lifestyle - Lemiyana, Lemiyana; Rusdi, Muhammad; Al Maraghy, Muhammad (IKONOMIKA, 2024)
The capital market in this technological era is often promoted by the government through the Indonesia Stock Exchange (IDX). This encourages the growth of investors, especially millennial investors. By conducting an empirical investigation into the mediating function of lifestyle between digital literacy and investment. Data was collected from 130 millennial investor in Palembang city. The data were analyzed using PLS-SEM analysis. The research results indicate that digital literacy  influences investment and lifestyle also affects investment. This study also shows lifestyle mediates the influence of digital literacy on investment.